THE EFFECT OF SECOND WAVE COVID-19 CONCERNS ON DISTRESS ON MILLENNIALS PARENTING - Eka Mariyanti; Nor Azilah Husin; Puti Embun Sari; Siska Lusia Putri (Journal of Islamic, Social, Economics and Development, 2021)
The second wave of the COVID-19 pandemic in Indonesia has increased the concerns of many people, coupled with the imposition of restrictions on community activities (PPKM) in the city of Padang, causing social and economic turmoil, which has caused tremendous pressure for many families, especially for working millennial parents. Experts warn that a minority of people may experience long-lasting mental health problems such as depression, anxiety, and stress longer than the pandemic itself. Previous studies with pandemic outbreaks have shown that media attention can increase anxiety and mental fatigue. Social isolation and restrictions on social activities can lead to improved online communication, and parents who use social media can be influenced by other people's emotions online. During Work From Home (WFH), the rate of meeting further people decreases. Indirectly, some Millennials parenting will spend their time with the virtual world. A lot of sad news shared on social media also has a significant impact on parents' mental health. The current study aims to examine COVID-19 concerns about Distress (Depression, Anxiety, and Stress) in millennial parents. Data were collected by online surveys advertised on social media with a sampling method using purposive sampling with the criteria of Millennials born in 1980-1991. Having children and living in the city of Padang, the sampling method used the help of the G*Power software and found 147 samples as respondents in this study. Data analysis by looking at the model and moderation using SEM-PLS. The results of the study prove that it turns out that Covid-19 worries do not make millennial parents in the city of Padang become stressed and depressed. The results only demonstrate that Covid-19 concerns only make millennial parents anxious.